The Cognitive Absurd Story The Formation Stage - ghilous, salah (El Omda in Linguistics and Discourse Analysis, 2022)
This article proposes a time frame for the emergence of the cognitive absurd story genre, which we define as a fictional genre with creative, cultural, and cognitive dimensions. It is extremely important and significant, since it contains moral and social content derived from heritage and history, as well as philosophy and mysticism. Its content is self-criticism, and a rebellion against the social situation, a precise criticism wrapped in symbol, irony, sarcasm, irrationality, and imagination, in which the writer invests his ideas and imaginative and creative energies, breaking the logic of time, with an interesting narrative technique that pleads with contradictions and antagonistic and strange dualities about absurdity through the actors and their relationships to each other , and the irrationality of the conflict in them. The writer does not present the events from a transparent perspective, and the characters are coded and unclear. As for the absurd, cognitive narrative perspective, it is open to multiple readings of the reader according to his knowledge and cultural knowledge. We seek, through this article, to lay the first brick of the genre of the absurd, cognitive story to fill the void in the short story in Algeria and the Arab world, and we are certain that this project will be accepted by the reader, and the book will take it further.